Factors Associated with Stunting Incidents in Toddlers - Anita, Sari; Novita, Nesi; Vasra, Elita (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
Stunting under five is a condition of failure to thrive in children under 5 years old due to chronic malnutrition and recurrent infectious diseases, especially in the first 1,000 days of life. Stunting arises as a result of malnutrition which has accumulated over a long period of time so that its physical manifestations will be more visible at the age of 24–59 months. Based on the framework of the causes of nutritional problems "The Conceptual Framework of the Determinants of Child Undernutrition" and "The Underlying Drivers of Malnutrition", prevention of stunting must focus on addressing the root causes of nutritional problems, both directly and indirectly. Purpose: To find out the situational analysis of stunting that occurs in toddlers at the Pembina Health Center in 2023. Method: This is a qualitative study, the sampling technique is purposive sampling, with criteria set by the researcher. This study used key informants, namely child health functional doctors and nutrition officers, as well as the main informants, namely 4 mothers who had stunted toddlers. Results: Obtained an overview of the situation of stunting in toddlers at the Pembina Health Center in 2023. Conclusion: All the main informants from stunting toddlers had low education, most of the informants had a history of infectious diseases, there were 2 informants who had a history of exclusive breastfeeding and 2 non-exclusive breastfeeding informants, there were informants who gave MP ASI at the age of 6 months, some were not right, income level The families of all informants were low, some parenting styles were supportive and some were not supportive, some were good and some bad care for mothers during pregnancy.